HIV stroke risk: evidence and implications. (March 2013) - Singer, Elyse J.; Valdes-Sueiras, Miguel; Commins, Deborah L.; Yong, William; Carlson, Margrit
An estimated 34 million men, women, and children are infected with human immunodeficiency virus type 1 (HIV-1), the virus that causes acquired immunodeficiency syndrome (AIDS). Current technology cannot eradicate HIV-1, and most patients with HIV-1-infection (HIV+) will require lifelong treatment with combined antiretroviral therapy (cART). Stroke was recognized as a complication of HIV-1 infection since the early days of the epidemic. Potential causes of stroke in HIV-1 include opportunistic infections, tumors, atherosclerosis, diabetes, hypertension, autoimmunity, coagulopathies, cardiovascular disease, and direct HIV-1 infection of the arterial wall. Ischemic stroke has emerged as a particularly significant neurological complication of HIV-1 and its treatment due to the aging of the HIV+ population, chronic HIV-1 infection, inflammation, and prolonged exposure to cART. New prevention and treatment strategies tailored to the needs of the HIV+ population are needed to address this issue.